2019
DOI: 10.37358/rc.19.2.6936
|View full text |Cite
|
Sign up to set email alerts
|

Luminal Versus Non-luminal Breast Cancer CDH1 Immunohistochemical Expression

Abstract: We investigated the immunohistochemical expression of E-cadherin (product of CDH1 gene) and its correlation with clinical-pathological parameters and survival rate in the molecular groups of breast cancer. Our study included female breast cancer patients diagnosed at the Municipal Emergency Clinical Hospital Timisoara followed up five years since diagnosis using formalin fixed paraffin embedded tissue. The traditional prognostic factors (age, tumor size, histological type, histological grade, anatomical status… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Activated partial thromboplastin clotting time (aPTT) is another assay that characterizes coagulation of the blood. Its value's reference range is between 30 s and 50 s [ 12 ]. Aspartate aminotransferase to platelet ratio index (APRI = {(AST/AST upper limit of normal range) x 100}/platelet count (109/L)) is supposed to be a novel accurate index for the prediction of significant fibrosis and cirrhosis [ [13] , [14] , [15] , [16] , [17] , [18] , [19] ].…”
Section: Methodsmentioning
confidence: 99%
“…Activated partial thromboplastin clotting time (aPTT) is another assay that characterizes coagulation of the blood. Its value's reference range is between 30 s and 50 s [ 12 ]. Aspartate aminotransferase to platelet ratio index (APRI = {(AST/AST upper limit of normal range) x 100}/platelet count (109/L)) is supposed to be a novel accurate index for the prediction of significant fibrosis and cirrhosis [ [13] , [14] , [15] , [16] , [17] , [18] , [19] ].…”
Section: Methodsmentioning
confidence: 99%
“…Besides the particular action, E- cadherin transduces signals from the extracellular field through the cytoplasmic end in the nucleus, modifying the gene expression. Epithelial morphology decreases and high invasiveness (meaning advanced phase, high grade and poor prediction/prognosis) is associated with the decrease or complete lack of E-cadherin found in various types of cancer (Zaha et al 2019). Lee et al (2010) demonstrated the inhibitory action of WA on activating the signal transducer; also, the activating role of transcription 3 in human breast cancer cells has been identified.…”
Section: Breast Cancermentioning
confidence: 97%
“…Moreover, Primary and Proliferous tumors have wild-type TP53. One of their most significant genes is CDH1, which is highly expressed in the luminal A and luminal B subtypes, while it has low activity in HER2 − positive and basal − like subtypes (Zaha et al, 2019). However, the higher rate of PR positive than PR negative in the Primary and Proliferous subtypes may differ from LuminalB tumors.…”
Section: Comparison Between Msdec and Pam50 Subtypesmentioning
confidence: 99%